STRATEGI KEUCHIK SEBAGAI PELAYAN PUBLIK DALAM MENINGKATKAN PARTISIPASI MASYARAKAT - Aduwina Pakeh (Jurnal Public Policy, 2017)
This paper aims to explain the alternative strategies that can be done by the Village Head (Keuchik) as public servants, especially those related to the service of population administration. Public services should continue to be improved and involve recipients of services. The problem is in the service process, in addition to the quality is still low, the public as recipients of services rarely included. The methods used in this study are qualitative and secondary data. It is found that there are at least two strategies that can be done in order to improve the service and public participation, such as the Citizen Charter and the application of information and communication technology. Based on these findings, Keuchik as public servant is expected to implement both strategies in providing and improving public services. Keywords: village, strategy, village head, public service, participation